Intelligence from secrets to policy - Lowenthal, Mark M. (Sage/CQ Press, 2012)
Intelligence veteran Mark M. Lowenthal details how the intelligence community's history, structure, procedures, and functions affect policy decisions. With straightforward and friendly prose, the book demystifies a complex process.